Dimerization of Sterol Regulatory Element-Binding Protein 2 via the Helix-Loop-Helix-Leucine Zipper Domain Is a Prerequisite for Its Nuclear Localization Mediated by Importin β - Nagoshi, Emi (American Society for Microbiology, 2001)
The sterol regulatory element-binding protein 2 (SREBP-2), a transcription factor of the basic helix-loop-helix-leucine zipper (bHLH-Zip) family, is synthesized in the form of a membrane-attached precursor molecule. When cells are deprived of sterols, a two-step proteolytic processing releases the transcriptionally active N-terminal segment of SREBP-2, thereby allowing it to enter the nucleus. In previous studies, we showed that the nuclear import of SREBP-2 occurs via the direct interaction of importin β with the HLH-Zip domain. In this study, in order to more completely understand the intracellular dynamics of SREBP-2, we focused on the manner by which importin β recognizes SREBP-2 at the initial step of the import. It was found that the active form of SREBP-2 exists as a stable dimer in solution and that the substitution of leucine residues for alanine in the leucine zipper motif disrupted the dimerization. It was also demonstrated that this mutant protein did not enter the nucleus either in vivo or in vitro. Solution binding assays, which involved the chemical cross-linking of wild-type or mutated SREBP-2 with importin β, revealed that the import-active complex appeared to be composed of a dimeric form of SREBP-2 and importin β. In addition, the SREBP-2 binding domain of importin β corresponded to an overlapping but not identical region for importin α binding, which may explain how importin β is able to recognize the dimeric HLH-Zip directly. These results indicate that dimerization is a prerequisite process for the nuclear import of SREBP-2 mediated by importin β.